Word-Formation Process (Morphology) Through the Maternal Reflective Method by Teacher towards Deaf Students in Grade V (Descriptive Study at SDLB Santi Rama) - Tiani Ayuningthias Zuhri; Riana Bagaskorowati; Leliana Lianty (Journal of ICSAR, 2021)
This research aims to gain in-depth information about the word-formation process (morphology) through the maternal reflective method in the fifth-grade deaf students at SDLB Santi Rama. This research uses a qualitative approach with a descriptive method. Data analysis of this research uses Miles and Huberman model that has three steps, namely data reduction, data presentation, and data verification or data conclusions. The data collection techniques in this research are interviews, observations, and document review. The result shows that the word-formation process (morphology), especially affixed words, is divided into three: forming prefixes, forming suffixes, and the morphophonemic process. The word-formation process (morphology) begins with two kinds of conversation that are perdati (conversation from the heart to heart) and percamsi (conversation to transmit some information). At the same time, the MRM principle used in word formation (morphology) is the process of discovery learning. Suggestions for this research are that teachers can maintain, improve, and apply the implementation of MRM to the word-formation process (morphology).